Dictionary of Biblical Theology - Thomas Kalayil (Journal of Dharma, 1977)
The Theological Publications in India (TPI) deserves unreserved gratitude for having made available to the Indian readers a very valuable volume so inexpensively priced: Dictionary of Biblical Theology. The volume is ideal for anyone who is interested in biblical theology. Throughout the work there is a scientific serenity, and in catering to the interests of the scholar the authors have not lost sight of the needs of the ordinary reader. It is, in other words, scientific and pastoral at the same time. It could be recommended for a vademecum not only to teachers and students of theology and the Bible, but also to preachers